2012
DOI: 10.1371/journal.pone.0047161
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Effects of Endostar in Combination with Oxaliplatin via Inhibition of HIF and CXCR4 in the Colorectal Cell Line SW1116

Abstract: Combination treatment with endostar, a novel modified endostatin, and cytotoxic chemotherapies showed a survival benefit in Chinese clinical trials. However, the exact mechanism for this synergism remains unclear. In this study, we report for the first time that the chemokine receptor CXCR4 and the hypoxia-inducible transcription factors (HIF)-1α and HIF-2α are involved in these synergistic antitumor effects in human colorectal cancer SW1116 cells in vitro when endostar treatment is combined with the cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…While highly homologous, HIF-1 α and HIF-2 α have unique tissue distributions and play critical but nonoverlapping roles in tumor progression [ 5 , 6 ]. HIF-2 α promotes metastasis through regulation of critical factors controlling tumor cell metastatic potential, such as CXCR4 and TWIST [ 7 9 ]. To date, studies have shown that HIF-2 α , TWIST, and CXCR4 are overexpressed in several human tumors such as clear cell renal carcinoma (ccRCC) [ 23 ], nonsmall cell lung cancer (NSCLC) [ 24 ], neuroblastoma [ 25 ], and breast, prostate, gastric, hepatocellular, colon, and bladder cancers [ 11 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While highly homologous, HIF-1 α and HIF-2 α have unique tissue distributions and play critical but nonoverlapping roles in tumor progression [ 5 , 6 ]. HIF-2 α promotes metastasis through regulation of critical factors controlling tumor cell metastatic potential, such as CXCR4 and TWIST [ 7 9 ]. To date, studies have shown that HIF-2 α , TWIST, and CXCR4 are overexpressed in several human tumors such as clear cell renal carcinoma (ccRCC) [ 23 ], nonsmall cell lung cancer (NSCLC) [ 24 ], neuroblastoma [ 25 ], and breast, prostate, gastric, hepatocellular, colon, and bladder cancers [ 11 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although highly homologous, HIF-1 α and HIF-2 α play critical but nonoverlapping roles in tumor progression [ 5 , 6 ]. Recent studies have shown that TWIST and CXCR4 are two direct target genes of HIF-2 α , HIF-2 α can activate the expression of TWIST and CXCR4, which subsequently promote invasion and metastasis of tumor cells [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endostar combined with radiation or chemotherapy has proven effective in treating other cancers, including nasopharyngeal carcinoma, colorectal, non-small cell lung and cervical cancers (2325). In addition, Chang et al (26) investigated the efficacy of endostar combined with chemotherapy on human esophageal squamous cell carcinoma Eca-109 cells in mice, and demonstrated that the tumor volumes and weight were significantly lower in the treatment group compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Some grade III and grade IV glioma samples that expressed relatively low HIF-2α levels also might indicate a better prognosis towards the patients. Some publications have stated that HIFs, including HIF-2α, correlate with the perception of chemotherapy resistance in several other cancers such as liver [22], lung [23], renal [24], and colorectal [25] cancer. According to those papers, HIF-2 is responsible for allowing a vigorous proliferation of the cancerous cells that further impede the drug's efficacy.…”
Section: B a G U S R A M A S H A A M A N G K U E T A Lmentioning
confidence: 99%